Current status of loquat in Chile - Fichet T.; Razeto B. (First international symposium on loquat, 2003)
The loquat is a minor fruit tree with very little development in Chile, with a planted area of nor more than 145 hectares. The irregular export of this fruit mostly goes to the east coast of the USA, the local market being its main consumer. The early varieties can reach the best price in the local market, whereas the late ones get a very low price when they have to compete with other fruits appearing at the beginning of the season.
1. International Symposium on Loquat, 2002/04/11-13, Valencia (Spain)